An Educational Management Model Based on the Exemplary Leadership of Prophet Muhammad (PBUH) as a Humanistic Learning Foundation - Diko Acun Pratama (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to provide an in-depth understanding of the development of a humanistic educational management model based on the exemplary leadership of Prophet Muhammad (PBUH), serving as both a conceptual and implementational foundation for modern Islamic education systems. His exemplary leadership is not only a normative guide but also a practical framework in educational management that holistically humanizes students. The research employs a qualitative approach with utilizing a literature review of classical texts, tafsir, hadith, the history of Islamic education, and contemporary studies on humanistic educational management. The findings indicate that the values of Tawhid (monotheism), noble character, compassion, justice, and wisdom exemplified by Prophet Muhammad (PBUH) form the foundational principles for building a holistic education system. This system goes beyond academic achievement, focusing on character development, social competence, and the spiritual growth of students. The implementation of this model is observed through several dimensions: educational leadership that prioritizes exemplary behaviour, a dialogical and participatory teaching system, a curriculum that integrates prophetic values, a humanistic evaluation system aligned with students' development, and the creation of a conducive learning environment focused on the common good. Further research is recommended to develop operational models and implementational tools for formal educational institutions, ensuring that prophetic values can be applied systematically, measurably, and sustainably.